PSIKOEDUKASI SEBAGAI PENDIDIKAN KARAKTER SOSIAL BEBAS BULLYING - Parihah Nurasiah, Sofa; Sapitri, Denisa; Kamalah, Lu'luatul; Fadillah Bahri, Aliffaldi; Zikri, Fahreza; Fahmi Median, Muhammad; Nauval Mubaarok, Muhammad; Jannah Wahiddin, Anbar; Abdillah, Rasa; Ilyasa Amrullah, Muhammad; Khoirun Nisa, Siti (ABISATYA DINAMIKA ISWARA PUBLISHING, 2024)
Bullying has emerged as a significant social problem in educational institutions causes severe psychological consequences for its victims, including depression and anxiety. This article aims to elaborate the role of psychoeducation as a comprehensive approach combat bullying among students. By integrating elements of education with psychological intervention, psychoeducation aims to increase self-awareness, personal growth, and the problem solving skills among students. This activity was carried out by students of Muhammadiyah University Bandung to SDN 2 Jati Garut Regency which focuses on providing education about the types of bullying and its impacts towards victims and perpetrators, as well as prevention strategies that must be implemented. This program involved audiences discussions, interactive activities, and utilized multimedia resources for foster awareness and proactive behavior against bullying. The findings show that initiatives like this are vital in creating a healthy social environment and intimidation free in school.